Brazil’s National System for the evaluation of Higher Education: context, challenges, and perspectives - Verhine, Robert Evan; Dantas, Lys Maria Vinhaes (Revista de Educação PUC-Campinas, 2021)
This article discusses the implementation of the National System for the Evaluation of Higher Education from its inception in 2004 to present times, paying special attention to the advances it achieved and the challenges that it must meet in the near future. After reviewing international perspectives on Higher Education quality assurance, the text examines adjustments to operationalize the implementation of the National System for the Evaluation of Higher Education model, highlighting the importance of improving the System’s self-evaluation component. The article concludes by addressing the challenges that must still be faced, such as the inclusion of state Higher Education systems in National System for the Evaluation of Higher Education, the improvement of indicators and external the evaluators, the effective utilization of the evaluation’s results, the need to distinguish evaluation processes from regulation policies, and the possibility of transforming the existing framework into a multidimensional evaluation model.